Physicochemical, structural, and functional properties of wampee (Clausena lansium (Lour.) Skeels) fruit peel pectin extracted with different organic acids. (30th August 2022) - Peng, Jian; Bu, Zhibin; Ren, Huiyan; He, Qi; Yu, Yuanshan; Xu, Yujuan; Wu, Jijun; Cheng, Lina; Li, Lu
Highlights: Acid types had a significant effect on the yield of wampee fruit peel pectic polysaccharide (WFPP) Sugar composition and branches of WFPPs could be modulated by acid types. Surface morphology and main structure of WFPPs was little changed by acid types. The emulsifying properties of WFPPs were higher than commercial citrus pectin. WFPP extracted by oxalic, acetic, or hydrochloric acid had better functional properties. Abstract: Effects of different extraction acids on physicochemical, structural, and functional properties of wampee fruit peel pectin (WFPP) were comparatively investigated. The hydrochloric acid extracted WFPP (HEP) exhibited the highest degrees of methylation (67.79%) and acetylation (86.29%) coupling with abundant monosaccharides and rhamnogalacturonan branches, but lowest molecular weight (5.58 × 10 5 Da). The results of SEM, X-ray diffraction, and Fourier transform infrared spectroscopy analyses showed that acid types had little effect on the surface morphology of WFPP. However, compared to commercial citrus pectin (CCP), several specific absorbance peaks (1539, 1019, 920 cm −1 ) were found in WFPPs, which corresponds to aromatic skeletal stretching, pyranose, and d -glucopyranosyl, respectively. Moreover, the rheological behavior revealed that WFPP solution was pseudoplastic fluid and affected by acid types. And the WFPPs exhibited higher emulsifying activity and emulsion stability than CCP. All these WFPPs presented well antioxidant activity and promoting probiotics ability, especially for HEP.